2018
DOI: 10.1111/idh.12363
|View full text |Cite
|
Sign up to set email alerts
|

Explorative study on quality of life in relation to salivary secretion rate in head and neck cancer patients treated with radiotherapy up to 2 years post treatment

Abstract: Patients with hyposalivation showed deterioration in health related quality of life (QoL) at 24 months compared with 12 months post RT. Most pronounced were problems with insomnia, swallowing, social eating, dry mouth, and sticky saliva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Their stimulated salivary secretion rate was determined at pretreatment and at 6 months, 1 year, and 2 years post treatment. Clinical status, minor gland secretion rates, stimulated whole salivary secretion rate and microflora on the tongue, buccal mucosa and supragingival plaque and quality of life has been reported previously [ 8 , 17 , 19 ]. In the present study, 29 patients were included.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Their stimulated salivary secretion rate was determined at pretreatment and at 6 months, 1 year, and 2 years post treatment. Clinical status, minor gland secretion rates, stimulated whole salivary secretion rate and microflora on the tongue, buccal mucosa and supragingival plaque and quality of life has been reported previously [ 8 , 17 , 19 ]. In the present study, 29 patients were included.…”
Section: Methodsmentioning
confidence: 87%
“…Both MUC7 and MUC5B are glycoproteins and can interact with oral microbes to facilitate their removal and/or reduce their pathogenicity [ 15 ]. Previous studies have shown that patients often report problems with sticky saliva after treatment of cancer of the head and neck region [ 16 , 17 ]. Our previous study showed that the concentration of MUC5B in stimulated saliva decreases to about 75% of the concentration seen in healthy controls with normal salivary secretion rate [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for cancer of the head and neck region may lead to late and/or chronic complications such as persistent xerostomia, low salivary secretion rate, sticky saliva, dysphagia, and trismus. (Almståhl et al, ; Deboni et al, ; Pauli et al, ) Due to decreased bone healing of irradiated bone, there is a risk of osteoradionecrosis, especially in patients who use tobacco or are alcohol abusers. (Epstein et al, ) In patients with low salivary secretion rate, there is an increased risk of caries.…”
Section: Discussionmentioning
confidence: 99%
“…Late side effects of cancer treatment are often irreversible and may occur several months to years after completed radiotherapy, for example, trismus, dysphagia, osteoradionecrosis, low salivary secretion rate, permanent xerostomia, and caries. (Almståhl, Finizia, Carlén, Fagerberg‐Mohlin, & Alstad, ; Almståhl, Skoogh Andersson, Alstad, Fagerberg‐Mohlin, & Finizia, ; Epstein et al, ; Moon et al, ; Pauli, Johnson, Finizia, & Andréll, )…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that radiation treatment for head and neck cancer as well as Sjögren’s syndrome hampers healthy salivary gland function, thereby decreasing saliva quality and quantity (hyposalivation; Pedersen et al 2002). This condition can lead to oral infections, pain, and deficient nutritional status and decrease the quality of life for afflicted patients (Almstahl et al 2019). However, because current available treatments, such as secretory agonists and saliva substitutes, provide only temporary relief (Noaiseh et al 2014), there is an urgent need to develop alternative long-term solutions (Ozdemir et al 2016).…”
Section: Introductionmentioning
confidence: 99%